Parenting Education Tentang Stunting pada Orang Tua Balita sebagai Upaya dalam Mencegah Terjadinya Stunting - Komsiyah Komsiyah; Achmad Syaifudin; Dian Nur Kumalasari; Ayu Dita Handayningtyas; Fhandy Aldy Mandaty; Sumarno Sumarno; Zaki Naufal Ramadhani; Yanuar Syah Rizky (Lembaga Pengembangan Kinerja Dosen, 2024)
Stunting is a growth and development disorder in children caused by a chronic lack of nutritious nutritional intake and due to the impact of various recurring infections, which is characterized by the child's length or height being below standard (< -2 SD). This Community Service aims to increase parental knowledge through parenting education activities for parents of children under five as an effort to detect early and prevent stunting. The service method is carried out by carrying out anthropometric measurements on toddlers and providing health education about stunting, including parenting patterns in preventing stunting. The results showed that there were 1 toddlers who were diagnosed with stunting out of 24 toddlers (4.17%). Parents of toddlers who took part in parenting education activities in this activity were very enthusiastic. It appears that out of the 24 parents who attended, 15 people asked about prevention and correct parenting patterns related to stunting toddlers. After this Community Service activity, it is hoped that parents will pay more attention to the nutritional needs of their toddlers, be active in posyandu activities so that if there are related problems, one of which is delayed growth in their children, they can be resolved immediately